The Twelfth Grade Students’ Error Analysis in Using Conditional Sentence Type I, II, III - Novarita Novarita (Universitas PGRI Semarang, 2017)
There were two problems of this study; first, what kinds of error, second, what were the factors of students’ errors in using conditional sentence type I, II, III. The objectives of this study were: 1) to find out kinds of errors, 2) to find out the factors of students’ error in using conditional sentence type I, II, III. The method used in this study was descriptive. The population was the twelfth grade students of SMK Negeri 4 OKU. The sample of this study was chosen through a random sampling. The total number of sample was 60 students. In collecting the data, the writer asked the sample students to translate 22 items of conditional sentence type I, II, III from Indonesian to English. The data were classified the table of errors in order to find out kinds of error. So, the result of this research showed that there were one thousand (1000) errors. The kinds of errors grouped into eleven (11) major categories namely: addition verb (ing), addition “be” (was), addition “be” (is), addition “punctuation” (comma), omission “will”, substitution (do became did), substitution (would became will), substitution “be” (were became was), substitution (should became will), substitution “verb”, disordering “ subject (i).Keywords: Error , Using , Conditional Sentence , type 1,2,3.